2022
DOI: 10.1136/thoraxjnl-2021-218068
|View full text |Cite
|
Sign up to set email alerts
|

Respiratory and allergic outcomes among 5-year-old children exposed to pesticides

Abstract: BackgroundLittle is known about the effects of pesticides on children’s respiratory and allergic outcomes. We evaluated associations of prenatal and current pesticide exposures with respiratory and allergic outcomes in children from the Infants’ Environmental Health Study in Costa Rica.MethodsAmong 5-year-old children (n=303), we measured prenatal and current specific gravity-corrected urinary metabolite concentrations of insecticides (chlorpyrifos, pyrethroids), fungicides (mancozeb, pyrimethanil, thiabendazo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“…Allergic rhinitis is known to be affected by various environmental factors such as season, region, and lifestyle 30 , 31 . Moreover, in previous studies investigating the association between harmful environmental factors and allergic rhinitis, a significant negative association was observed for substances such as bisphenol S, vanadium, and 3,5,6-trichloro-2-pyridinol 32 34 . Considering these findings, the lack of consistent associations observed in this study may be due to differences in variables of the study environment that were not examined.…”
Section: Discussionmentioning
confidence: 91%
“…Allergic rhinitis is known to be affected by various environmental factors such as season, region, and lifestyle 30 , 31 . Moreover, in previous studies investigating the association between harmful environmental factors and allergic rhinitis, a significant negative association was observed for substances such as bisphenol S, vanadium, and 3,5,6-trichloro-2-pyridinol 32 34 . Considering these findings, the lack of consistent associations observed in this study may be due to differences in variables of the study environment that were not examined.…”
Section: Discussionmentioning
confidence: 91%
“…30,31 Moreover, in previous studies investigating the association between harmful environmental factors and allergic rhinitis, a signi cant negative association was observed for substances such as bisphenol S, vanadium, and 3,5,6-trichloro-2pyridinol. [32][33][34] Considering these ndings, the lack of consistent associations observed in this study may be due to differences in variables of the study environment that were not examined.…”
Section: Discussionmentioning
confidence: 69%
“…Several studies have found associations between pesticide exposure and the development of asthma, particularly in children. Pesticides used in agriculture, such as organophosphates and pyrethroids, have been linked to an increased risk of asthma in children living near agricultural areas [ 232 , 233 ]. Pesticides produce asthma symptoms that include edema, irritation, endocrine disruption, and immunological suppression [ 232 , [234] , [235] , [236] ].…”
Section: Resultsmentioning
confidence: 99%